The position of biologic therapies in the treatment of non-infectious uveitis. Part I - Waszczyk-Łączak, Maja; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Non-infectious uveitis is a heterogeneous group of diseases, which share a common denominator, that is, the inflammation within the structure of the eye. The goal of treatment in non-infectious uveitis is to inhibit the abnormal immune response. Glucocorticoids are still the basic therapy followed by immunosuppressants should there be no response to the first line treatment. Systemic biologic agents are another alternative. Biological therapy involves the administration of substances intended to bind to the specific molecules which trigger the inflammatory response. Biologic agents are defined as bioengineered receptor complexes, antibodies, Fab fragments, and agents such as interferons that affect the expression of pro-and anti-inflammatory components of the immune system. In the article, TNF inhibitors (Tumor Necrosis Factor) – infliximab, adalimumab, etanercept, golimumab and certolizumab pegol will be presented. Tumor Necrosis Factor (TNFα) is a cytokine involved in the normal inflammatory response to an infection or an injury. However, its elevated concentrations can cause an excessive inflammatory response which destroys tissue.